CONSCIENTIZAÇÃO AMBIENTAL NO ENSINO DE CIÊNCIAS - Reginatto, Vanessa P.; Mors, Marlete F.; Jasper, André; Oliveira, Eniz C.; Harres, João B. S.; Auth, Milton A.; Marchi, Miriam I.; Konrad, Odorico (Salão do Conhecimento, 2013)
Resumo